A handbook for construction planning and scheduling - Baldwin, Andrew, 1950- 4 0 16; Bordoli, David; 5 (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
The authoritative industry guide on good practice for planning and scheduling in constructionThis handbook acts as a guide to good practice, a text to accompany learning and a reference document for those needing information on background, best practice, and methods for practical application. A Handbook for Construction Planning & Scheduling presents the key issues of planning and programming in scheduling in a clear, concise and practical way. The book divides into four main sections: Planning and Scheduling within the Construction Context; Planning and Scheduling Techniques and Practices; Planning and Scheduling Methods; Delay and Forensic Analysis. The authors include both basic concepts and updates on current topics demanding close attention from the construction industry, including planning for sustainability, waste, health and safety and Building Information Modelling (BIM).The book is especially useful for early career practitioners - engineers, quantity surveyors, construction managers, project managers - who may already have a basic grounding in civil engineering, building and general construction but lack extensive planning and scheduling experience. Students will find the website helpful with worked examples of the methods and calculations for typical construction projects plus other directed learning material.This authoritative industry guide on good practice for planning and scheduling in construction is written in a direct, informative style with a clear presentation enabling easy access of the relevant information with a companion website providing additional resources and learning support material. the authoritative industry guide on construction planning and scheduling direct informative writing style and clear presentation enables easy access of the relevant information companion website provides additional learning material. --;A Handbook for Construction Planning & Scheduling presents the key issues of planning and programming in scheduling in a clear, concise and practical way--
Includes bibliographical reference (pages 389-398) and index.
Keywords: 2 -- 0; 6; Superintendence. -- Building;Production scheduling. -- 20; 20; 2